2021
DOI: 10.3390/ijerph182010848
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on Minimum Foot Clearance Measurement: Sensing Modalities

Abstract: Background: Falls are a major public health issue and tripping is the most common self-reported cause of outdoor falls. Minimum foot clearance (MFC) is a key parameter for identifying the probability of tripping. Optical motion capture systems are commonly used to measure MFC values; however, there is a need to identify alternative modalities that are better suited to collecting data in real-world settings. Objective: This is the first of a two-part scoping review. The objective of this paper is to identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, based on Figure 3 , we can conclude that the foot height during the initial swing phase is lower in fallers than in non-fallers. Many previous studies have focused on minimum toe clearance (i.e., foot height) during the mid-swing phase in fallers and non-fallers ( Chiba et al, 2005 ; Khandoker et al, 2008b , 2008a ; Barrett et al, 2010 ; Karmakar et al, 2013 ; Cebolla et al, 2015 ; Watanabe, 2018 ; Delfi et al, 2021 ). However, based on our results, we consider it important to focus on foot height during the initial swing phase (e.g., maximum toe clearance) to assess fall risk instead of focusing on foot height during the mid-swing phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, based on Figure 3 , we can conclude that the foot height during the initial swing phase is lower in fallers than in non-fallers. Many previous studies have focused on minimum toe clearance (i.e., foot height) during the mid-swing phase in fallers and non-fallers ( Chiba et al, 2005 ; Khandoker et al, 2008b , 2008a ; Barrett et al, 2010 ; Karmakar et al, 2013 ; Cebolla et al, 2015 ; Watanabe, 2018 ; Delfi et al, 2021 ). However, based on our results, we consider it important to focus on foot height during the initial swing phase (e.g., maximum toe clearance) to assess fall risk instead of focusing on foot height during the mid-swing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that some variables related to foot position and angle during gait (e.g., sagittal foot angle at heel contact ( Chiba et al, 2005 ), minimum toe clearance ( Chiba et al, 2005 ; Delfi et al, 2021 ), stride length ( Kerrigan et al, 2000 ; Lee and Chou, 2006 ; Newstead et al, 2007 ), and variability of stride length ( Reelick et al, 2011 ; Doi et al, 2020 ; Bytyçi and Henein, 2021 ) are significantly different between non-fallers and fallers. This knowledge is beneficial for identifying the characteristics of older adults who are prone to falls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delfi et al [16,17] reviewed sensor technologies for MFC detection suitable for integration into wearable assistive devices; when considering cost and ease of use, inertial measurement units (IMUs) were the preferred application. Linear acceleration and angular velocity can be recorded from IMUs, and by double integrating the acceleration data (m/s 2 ), the critical foot displacement (m) can be computed.…”
Section: Introductionmentioning
confidence: 99%
“…Falls during walking put older adults at risk of serious injuries, e.g., fractures, brain injuries, or even death [ 1 3 ]. Trips are the most prevalent known cause of outdoor falls [ 4 ] and are considered to be the most challenging of falls [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%